Variability of leaf traits in natural populations of Picea omorika determines ignitability of fresh foliage - Popović, Zorica; Vidaković, Vera; Janković, Jovana (Frontiers in Forests and Global Change, 2023)
Introduction A variety of plant traits, from architectural to the cellular level, have been connected to flammability, but intraspecific variability of plant traits (ITV) and components of flammability is poorly studied. The lack of knowledge about ITV of plant traits related to flammability appears to be a major shortcoming in further interpreting species flammability and fire behavior and incorporating the data into models. Methods Morpho-ecophysiological traits (width, length, thickness, weight, area, volume, moisture content, flatness, specific leaf area, density of leaf tissue, ratio of area to volume) and time-to-ignition of fresh foliage were measured in seven populations of Picea omorika. Results All leaf traits are presented along with their correlations to the flammability trait. The seven populations differed in terms of fresh leaves’ time-to-ignition. Differences among populations in morpho-ecophysiological traits were also significant but not consistent among populations. PCA classified 49 elements into three different groups, where three populations were clustered by higher leaf area-related traits, other three populations were clustered by higher leaf length, volume, thickness, time-to-ignition, density index, moisture content, width, weight, and one population was classified between the two main groups. The first two principal components accounted for 87% of the total variance: variability in leaf area- and leaf weight-derived parameters (specific leaf area and density index) and time-to-ignition primarily defined the formation of the first axis, while variability in leaf flatness (based on leaf weight and thickness) primarily contributed to the formation of the second axis. Discussion Results suggest high ITV in natural populations of P. omorika regardless of site fire history.